An Empirical Study of Attitude Toward Cause Related Marketing Programs Among Young Indian Consumers - Thakur, Chandan (Indian Journal of Marketing, 2014)
Cause related marketing (CRM) has become an accepted marketing promotional tool and ,therefore, organizations from different parts of the world have started using it. The attitude of consumers toward CRM plays a significant role in the success and effectiveness of cause related marketing programs (CRMPs). Not enough research has been done in India to understand the attitude of consumers toward CRMPs and the implications they have for marketers, though some studies have been done in Western countries. This study is a pioneering empirical research to understand the attitude toward CRMPs among young Indian consumers and the implications for marketers. The study found that the overall attitude of young Indian consumers toward CRMPs was very positive and ,therefore, young Indian consumers can certainly be a good market segment to be targeted by the marketers. Another important finding showed that the attitude of young Indian consumers toward the products associated with CRM was very positive and ,therefore, products used by young consumers can be selected by marketers for CRMPs. However, the findings provided two important cautions for marketers. The marketers should not charge higher prices for the products associated with CRM as it was found that a majority of the young consumers were not willing to pay a higher price for products associated with CRM. It was also found that the young consumers were skeptical toward the advertisements related to CRMPs and ,therefore, marketers should understand that only genuine intent and commitment for a cause can make CRMPs successful and effective.